Preparation and Characterization of a Single-Walled Aluminosilicate Nanotube-Iron Oxide Composite: Its Applications to Removal of Aqueous Arsenate - Escudey-Castro, A; Escudey-Castro, A; Pizarro-Arriagada, C; Pizarro-Arriagada, C (2014)
A chemical method to synthesize a magnetite coating on aluminosilicate nanotubes (imogolite) that can be used as a magnetic adsorptive composite is reported via a new procedure based on impregnation with excess of solvent. This produced a nanocomposite of imogolite and magnetite, retaining at least two of the individual properties of its initial chemical species, which are determinant for some technological applications: large surface area and high saturation magnetization. Comparatively significant differences in terms of electrophoretic and magnetic characteristics were found between the direct solid mixture of the starting materials and the resultant imogolite-magnetite mixture. The adsorption kinetics of arsenate is described adequately by the pseudo-second model and the maximum adsorbed amounts (qe) of this anion were closed to those obtained experimentally. A high rate of arsenate adsorption on Fe-imogolite was initially observed, suggesting that the formation of new surface sites qualitatively and quantitatively improve the removal of arsenate. The combined use of different characterization techniques (XRD, TEM, Mössbauer spectroscopy, EM, VSM and SQUID) and the kinetic sorption study suggest that Fe-imogolite has a large potential for the treatment of arsenate polluted water or other nanotechnological applications, due to its high chemical reactivity. © 2013 Elsevier Ltd.